Inflation determinants and its effect on economic growth: The case of Lebanon - Saab, Rasha; Taher, Hanadi (Edelweiss Applied Science and Technology, 2025)
This study examines the factors influencing inflation and how it affects Lebanon’s economic growth using annual data from 1990 to 2022 through the ARDL technique. The current study employs the ARDL model under the Pesaran, et al. [1] testing approach, the Augmented Dickey-Fuller (ADF) test, and additional diagnostic tests to ensure no serial correlation or heteroscedasticity. It also applies CUSUM, CUSUM Square, and Ramsey tests to assess the impact of inflation on Lebanon’s economic growth. Under the ARDL assumptions, the study demonstrates that household consumption and government debt have a significant, long-term, positive influence on inflation but do not influence inflation over the short term. Other findings show that the rate of inflation has an adverse effect on both long- and short-term economic growth. Researching inflation and its impact on economic growth is vital to understanding how price levels affect economic stability. Inflation shapes policies, influences investments, affects purchasing power, and determines the long-term sustainability of growth. Accordingly, stable inflation fosters sustained development. The findings guide policymakers in managing consumption and debt to control inflation, while helping central banks curb inflation to support sustainable economic growth in Lebanon.